International Entrepreneurship: The Intersection of Two Research Paths - McDougall, Patricia P.; Oviatt, Benjamin M. (Academy of Management Journal, 2000)
Reflecting the internationalization of the marketplace and the increasing prominence of entrepreneurial firms in the global economy, the research paths of international business and entrepreneurship are intersecting with increasing frequency. International business researchers are broadening their traditional focus on large multinational companies to also include entrepreneurial firms in their research agendas. Cross-border business activity is of increasing interest to entrepreneurship researchers, and accelerated internationalization is being observed in even the smallest and newest organizations. This Special Research Forum on International Entrepreneurship reflects the fusion of these two areas and the developing worldwide academic interest in this topic.